Knowledge Translation and Teamwork Interventions to Optimize Intraoperative Processes of Care and Patient Outcomes - Khan, Hira (Université d'Ottawa / University of Ottawa, 2023)
The operating room (OR) is a high-risk environment that requires OR personnel to have up to date evidence-based technical and teamwork skills to maintain patient safety and consistent workflow. Despite anesthesiologists’ significant role in surgical patient safety, there is practice variation and a lack of evidence translation among anesthesiologists. Our first review synthesized current evidence on Knowledge Translation Interventions (KTIs) in anesthesiology during the intraoperative period. We found that education was the most effective KTI followed by reminder and audit & feedback. The second systematic review synthesized the current evidence on teamwork interventions in the OR setting and identified which change strategies were used to target which teamwork behaviour barriers/enablers using the Theoretical Domains Framework. Our findings inform evidence to optimize practice standardization in anesthesia and enhance surgical patient safety. Both reviews identify future directions for knowledge translation research and provide guidance on designing more effective and reproducible teamwork interventions.
Keywords: Knowledge Translation; Teamwork Interventions; Anesthesiology; Intraoperative care